Potentiostatically Poised Electrodes Mimic Iron Oxide and Interact with Soil Microbial Communities to Alter the Biogeochemistry of Arctic Peat Soils - Elliot Friedman; Kimberley Miller; David Lipson; Largus Angenent (Minerals, 2013)
Dissimilatory metal-reducing bacteria are ubiquitous in soils worldwide, possess the ability to transfer electrons outside of their cell membranes, and are capable of respiring with various metal oxides. Reduction of iron oxides is one of the more energetically favorable forms of anaerobic respiration, with a higher energy yield than both sulfate reduction and methanogenesis. As such, this process has significant implications for soil carbon balances, especially in the saturated, carbon-rich soils of the northern latitudes. However, the dynamics of these microbial processes within the context of the greater soil microbiome remain largely unstudied. Previously, we have demonstrated the capability of potentiostatically poised electrodes to mimic the redox potential of iron(III)- and humic acid-compounds and obtain a measure of metal-reducing respiration. Here, we extend this work by utilizing poised electrodes to provide an inexaustable electron acceptor for iron- and humic acid-reducing microbes, and by measuring the effects on both microbial community structure and greenhouse gas emissions. The application of both nonpoised and poised graphite electrodes in peat soils stimulated methane emissions by 15%–43% compared to soils without electrodes. Poised electrodes resulted in higher (13%–24%) methane emissions than the nonpoised electrodes. The stimulation of methane emissions for both nonpoised and poised electrodes correlated with the enrichment of proteobacteria, verrucomicrobia, and bacteroidetes. Here, we demonstrate a tool for precisely manipulating localized redox conditions in situ (via poised electrodes) and for connecting microbial community dynamics with larger ecosystem processes. This work provides a foundation for further studies examining the role of dissimilatory metal-reducing bacteria in global biogeochemical cycles.